Pengembangan Sistem Informasi E-report dan Monitoring Laporan Bulanan(LB1) Penyakit Berbasis Web (Studi Kasus: Puskesmas Dinoyo) - Muzdalifah Yully Ayu; Adam Hendra Brata; Marji Marji (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Monthly report (LB1) is disease data report containing ICD-10 data code, distribution of disease cases according to age group, and new cases or old cases. The report of disease data has done routine in every month, quarter, and annual report. The problem of Public Health Center Dinoyo in recording and reporting are still manual or conventional way to process, maintain, and deliver the report. The average amount of disease data at the Dinoyo Public Health Center was recorded 2000 - 3000 in every month by use manual system and it caused the record taking long time process, incomplete data so that it affected on the accuracy of LB1. Furthermore, late delivery of the report made the Health Office of Malang City could not monitoring, evaluating, and have difficulty to know the public health center's around Indonesia which not sent the report. Based on these problems is built the system based on website with waterfall model development, Codeigniter framework, and PHP programming language. The result is information system can be used for managing medical records, monthly report (LB1), and monitoring the monthly report (LB1). Based on the testing that has been done produce 100% valid value on unit testing, integration, and validation which shows that the system function already fulfilling the needs. The result of usability test is using usability scale system method obtained the score up to 77 which could be concluded the system has been acceptable and has provided user convinience.